Notes on the First Luther’s Concept of the Church in Ecumenical Perspective - Sörgel, Rainer (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
This study analyzes the concept of the Church in the early Luther based on his polemical writing Von dem Papstthum zu Rom wider den hochberühmten Romanisten zu Leizpig («Concerning the Roman Papacy against the very famous Romanist of Leipzig»), 1520. The article briefly expounds the principle characteristics of the concept of the Church in Luther, pointing out on the one hand the evident application of the theology of justification to the concept of the Church, and on the other hand the bi-dimensionality (spirit, body) of the Church in Luther. The reading of this analysis from the perspective of the current ecumenical dialogue reveals a notable similarity of the problem of the Church. Today, as in Luther’s time, the Catholic and Protestant traditions relate soteriology and the Church with different priorities. The analysis suggests the conclusion that the VPR supports the current proposal of understanding the interdependence between justification and Church as a possible common denominator for dialogue between the two traditions.
Keywords: theology of justification; spiritual church; ecclesiocentrism; fundamental ecclesiological difference; sacrament of salvation